Survey of some land snails in Jabel El-Akhdar area, Libya and the damage caused by Theba pisana To Brassica olerace - Bou fatoum, Marim salah (Al-Mukhtar Journal of Sciences, 2011)
A study was conducted to survey some species of land snails in AL-Jabel El-Akhder area, and The damage caused by feeding of Theba pisana on cabbage plant Brassica Oleracea , also showed some damage to vegtables croup, Fruit trees and aruamental plant. reared in plastic container, snails were fed with pieces of Brassica olerace. The study indecated that Theba pisana, Helix aspersa, Rumina decollate Achatina fucica , and Eermina desrtorun. During the rearing in the laboratory we observed that the eggs of Theba pisana,and Rumina decollate. The results showed that there is significant difference in the damage index based on the age of plant, age of snails and density of snails on plant. The young snails were not serious pest on plant. Leaf edges were the parts that were normally damaged.